Pengaruh Insentif Pajak dan Growth Opportunity Terhadap Konservatisme Akuntansi Pada Perusahaan Manufaktur Yang Bergerak di Bidang Industri dan Konsumsi yang terdapat di Bursa Efek Indonesia Pada Tahun 2020 - 2021 - Rizka Krisna Yulia (Universitas Katolik Widya Karya Malang, 2023)
Accounting conservatism as a precautionary principle in financial reporting where companies are not in a hurry to recognize, measure assets and profits and immediately recognize losses and debts that have the possibility of occurring. This study aims to determine the effect of tax incentives and growth opportunities on accounting conservatism in manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange for the period 2020 - 2021. The samples in this study were 20 manufacturing companies in the consumption industry sector over a period of 2 years. Data analysis was carried out by descriptive analysis then followed by the classic assumption test in the form of a normality test, multicollinearity test, heteroscedasticity test, autocorrelation test then for hypothesis testing a partial t test was carried out. The result of the partial test t of the tax incentive variable is 0.121 with a significance level of 0.904. Significance value of 0.904 > 0.05 which indicates that tax incentives have no effect on accounting conservatism. The result of the t partial test for the growth opportunity variable is 1.014 with a significance level of 0.317. Significance value 0.317 > 0.05. Based on these results, it can be stated that growth opportunity has no effect on accounting conservatism.